2020
DOI: 10.1002/ieam.4249
|View full text |Cite
|
Sign up to set email alerts
|

A Transdisciplinary Methodology for Introducing Solar Water Disinfection to Rural Communities in Malawi—Formative Research Findings

Abstract: This article is part of the special series "Improving Water Security in Africa." The work is the culmination of 7 Horizon 2020 projects focused on the environmental and social challenges of improving water security in African countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Noticeably these practical aspects play an important role in water source preference, and it is important to address existing concerns associated with safe sources through infrastructural improvements, and health promotion initiatives. Similarly, our results support previous findings that water treatment and management promotion must be behaviour centered and context appropriate, taking into consideration the needs and wants of the community it is targeting [24,[27][28][29][30][31][32]. Capacity in households and communities to monitor drinking water quality through practical and cost-effective methods, could re-enforce these messages in a more effective manner, as has been achieved with visual behaviour change techniques (e.g., Glo Germ ™ ) used elsewhere in Malawi [33][34][35].…”
Section: Discussionsupporting
confidence: 90%
“…Noticeably these practical aspects play an important role in water source preference, and it is important to address existing concerns associated with safe sources through infrastructural improvements, and health promotion initiatives. Similarly, our results support previous findings that water treatment and management promotion must be behaviour centered and context appropriate, taking into consideration the needs and wants of the community it is targeting [24,[27][28][29][30][31][32]. Capacity in households and communities to monitor drinking water quality through practical and cost-effective methods, could re-enforce these messages in a more effective manner, as has been achieved with visual behaviour change techniques (e.g., Glo Germ ™ ) used elsewhere in Malawi [33][34][35].…”
Section: Discussionsupporting
confidence: 90%
“…This, according to the finding of the study, is an important motivator for sustained water treatment behaviors. 23 In the present study, it was found that people were more likely to adopt treatment technologies that were considered to be easy to access and use. Products deemed sluggish, for instance, emerged as examples of undesirable forms of water treatment technologies throughout FGDs.…”
Section: Discussionmentioning
confidence: 51%
“…This, according to the finding of the study, is an important motivator for sustained water treatment behaviors. 23 …”
Section: Discussionmentioning
confidence: 99%
“…This cluster focuses on the purification of water for drinking purposes, including in this category the distinction between female and male, as well as adults, adolescent, infant or child and preschool child. It is known that gender roles need to be taken into consideration for interventions such as SODIS to be successful [55], and adverse effects observed from some toxic compounds in water are highly dependent on gender [56]. However, we have not detected any studies that address the inclusion of gender perspective into the investigation of water disinfection mediated by solar radiation.…”
Section: Yellow Clustermentioning
confidence: 84%